Union Mergers in Hard Times: The View From Five Countries - Solomon, Norman A. (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Union Mergers in Hard Times: The View From Five Countries," by Gary N. Chaison.
Keywords: Acquisitions & mergers; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z